Kolaborasi Pemerintah Dan Pelaku Usaha Sulawesi Tengah Untuk Mengembangkan Komoditas Rumput Laut - Andi Mardiana; Andi Salwa Sahnitasari; Iyanti Lahardi; Fahri Afdal (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
Central Sulawesi, one of the largest seaweed-producing provinces in Indonesia after South Sulawesi, but only uses seven per cent of its potential cultivation land. Despite its large production, the quality of Central Sulawesi seaweed is low due to a lack of coordination between the government and seaweed entrepreneurs, both in cultivation, post-harvest management, distribution, and marketing. To overcome this problem, development efforts are needed through the cooperation of local governments and business actors. This qualitative research aims to analyse the development of seaweed production quality and yield in Central Sulawesi with a focus on such cooperation. Recommended measures include improving production quality in Morowali and Banggai Laut districts, providing storage and transport, establishing processing industries, and zoning cultivation.